The research on the impact assessment of visual landscape of country parks In Beijing - Liu, Chuanan; Qi, Tong; Ma, Xiao (Journal of Environmental Engineering and Landscape Management, 2016)
The attribute of a country park and its visual environment are not only influenced by the distance from the park to the downtown area, but also the degree of urbanization.  Based on the landscape geography, landscape ecology, landscape aesthetics theories and the Guideline for Technical Review of Environmental Impact Assessment of Construction Projects (HJ 616-2011) and aiming to evaluate the visual quality of the country parks, we put forward three first-grade indicators (visual sensitive capacity, visual space capacity and visual absorption capacity) and seven second grade indicators (sighting distance, visual disturbance frequency, green looking ratio, inter-visibility, openness, relative angle and the relative area of artificial matrix) in our research. By virtue of the established entropy weight method model, combined with field data, the quantitative research of the visual environment of landscape in country parks was carried out so that the visual quality of the park can be improved. At same time, this can also provide a scientific basis for spatial planning of urban fringe area and repositioning of the park attribute.